Semiotic Analysis of Hal Kunta Ta'lam Poem by Faruq Juwaidah Based on Michael Riffaterre's Perspective - Maulidiyah, Shinta; Yurisa, Penny Respati (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
This study aims to analyze the poem